(untitled) (Journal of Scientific Research, 2020)
The aim of the present investigation was to quantify the detoxification and stress enzymes’ levels and correlate it with insecticides resistance in different age groups of Bactrocera cucurbitae population. Different age groups of insect population were isolated and processed for enzymes assay and survival analyses.The increase in the activities of CytP450, esterase and superoxide dismutase (SOD) have been observed till certain age and thereafter they decreased. However, activity of glutathione-S-transferase (GST) and catalase did not increase with age. Results of survival assay showed that deltamethrin and malathion caused higher mortality in the 15-days old (100%) insects than the 1-day old adult insects. Highest survival percentage after deltamethrin treatment was found in 7 days old insects, whereas malathion treated insects’ survival was maximum in 3 days old insect population. Based on the above results, it is inferred that lack of sufficient GST and catalase cause decrease in the resistance of B. cucurbitae with advancing age.